Learning from conflict in higher education - Simões, E.; Rosado-Pinto, P.; Almeida, F. (INTED2015 Proceedings 9th International Technology, Education and Development Conference, 2015)
Due to its structural complexity, and its openness to diversity, universities are proneto conflict, and invest an enormous amount of time and energy to reconcile divergent interests. Thus, conflict is an integral part of academic life, including the classroom, although in this latter case, it is seen as an uncomfortable issue. In fact, as teachers rarely assume that do not have control of their classes, as actually happens often, conflict in the classroom is a matter whose discussion tends to be avoided to not harm the personal and organizational image. As a result, teachers have little or no training to deal with these problems. Although students and teachers may differ on the extent and significance of inappropriate behaviors in the classroom, the extant literature on this issue indicates that there is some consensus on the fact that interpersonal conflicts often result from the interaction between students' "uncivilized" acts and teachers' negative approaches. This presentation focus on the crucial skills to deal constructively with these problematic situations, through two complementary directions. Firstly, we present the foundations of an intervention model for dealing with conflicts among students and between them and the teachers, in order to minimize the negative impact on relationships, and simultaneously take advantage of the learning potential of well managed conflicts, guiding its resolution for a solution-finding process. Secondly, we discuss the concept of "problem" as a central tool of a pedagogical strategy to stimulate learning from the resolution of didactically relevant cases, which are based on real situations taken from and similar to those that students will encounter in a professional context. These problems are always presented under the format of cognitive conflicts, and embedded in a specific context. Through a sequential approach, cognitive conflicts contribute to a meaningful learning that facilitates the acquisition of knowledge and the discovery of its applicability. A case in the field of management education to illustrate the method is presented and discussed in the framework of Problem-Based Learning (PBL) strategies.